(untitled) (Revista de Artes Marciales Asiáticas, 2012)
In this article, suggestions are given “how to” write and photograph martial arts techniques for publication. The aim is to improve the instructional and archival quality of martial arts books and articles. These suggestions are based on the author’s reviews of books showing movement, his experience in writing martial arts books (and from mistakes made in these efforts), and from his experience as a medical-technical writer and instructional designer. Simply thinking about how to present a martial art in print will help you understand and teach them: you will find it a valuable and rewarding exercise, even if you never publish the results.